Military Service Member and Veteran Reintegration: A Conceptual Analysis, Unified Definition, and Key Domains - Elnitsky, Christine A.; Fisher, Michael P.; Blevins, Cara L. (Frontiers in Psychology, 2017)
Returning military service members and veterans may experience a variety of stress-related disorders and challenges when reintegrating from the military to the community. Facilitating the reintegration, transition, readjustment and coping, and community integration, of military service members and veterans (MSMVs) is a societal priority. To date, research addressing MSMV reintegration has not identified a comprehensive definition of the term or defined the broader context within which the process of reintegration occurs although both are needed to promote valid and reliable measurement of reintegration and clarify related challenges, processes, and their impact on outcomes. Therefore, this principle-based concept analysis sought to review existing empirical reintegration measurement instruments and identify the problems and needs of MSMV reintegration to provide a unified definition of reintegration to guide future research, clinical practice, and related services. We identified 1,459 articles in the health and social sciences literature, published between 1990 and 2015, by searching multiple electronic databases. Screening of abstracts and full text review based on our inclusion/ exclusion criteria, yielded 117 articles for review. Two investigators used constant conceptual comparison to evaluate relevant articles independently. We examined the term reintegration and related terms (i.e., transition, readjustment, community integration) identifying trends in their use over time, analyzed the eight reintegration survey instruments, and synthesized service member and veteran self-reported challenges and needs for reintegration. More reintegration research was published during the last 5 years (n= 373) than in the previous 10 years combined (n= 130). The research suggests coping with life stresses plays an integral role in military service member and veteran post-deployment reintegration. Key domains of reintegration include individual, interpersonal, community organizations, and societal factors that may facilitate or challenge successful reintegration, and results suggest that successful coping with life stressors plays an integral role in post-deployment reintegration. Overall, the literature does not provide a comprehensive representation of reintegration among military service members and veterans. Although previous research describes military service member and veteran reintegration challenges, this concept analysis provides a unified definition of the phenomenon and identifies key domains of reintegration that may broaden our understanding and guide reintegration research and practice.